2014
DOI: 10.1080/02615479.2014.962019
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Care Leavers (Post-care Adults) in Social Work Education

Abstract: This paper explores the experiences of social work students on qualifying degree programmes in the UK who have previously been in care or 'looked after.' Using a sample drawn from three social work programmes in the North West of England, a semi-structured interview schedule was constructed, with the support of social workers who had been in the care systems, to examine the individual journeys of 11 students. This paper aims to explore, with this group of students, how their experiences relate to their decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Our study evidences strongly that course choice is closely related to childhood experiences for this group of young people. This was similarly reflected in the study by Mayall et al (2015) who conducted interviews with 11 social work students who had been in care. The students had been cautious about disclosing their care status on their application form, and once on the course, were selective about who they told.…”
Section: 'When I Become a Social Worker I Can Reflect Back On My Ementioning
confidence: 79%
“…Our study evidences strongly that course choice is closely related to childhood experiences for this group of young people. This was similarly reflected in the study by Mayall et al (2015) who conducted interviews with 11 social work students who had been in care. The students had been cautious about disclosing their care status on their application form, and once on the course, were selective about who they told.…”
Section: 'When I Become a Social Worker I Can Reflect Back On My Ementioning
confidence: 79%
“…The figured world lens highlights the assumption that all students have experienced a smooth upbringing without any life changing and traumatic experiences, resulting in pedagogical delivery that implies that issues discussed happen to 'other people' outside of the classroom. However, Ward et al (2017) and Mayall et al (2015) discuss how a number of care-experienced social work students found particular aspects upsetting, including a deterministic approach to teaching attachment theory, a focus on poor outcomes from care or emphasising the negatives of corporate parenting. The students felt that such approaches consistently denigrated care experiences and portrayed them as entirely lacking.…”
Section: Curriculamentioning
confidence: 99%
“…In this paper, we argue that the figured world lens helps us to understand how negative interpretations of care‐experienced students can serve to make their lives more difficult. We know that care‐experienced students face some of the most pronounced marginalisation (Hauari et al, 2019) resulting in many resisting this label completely or until later in their HE journey (Mayall et al, 2015; Pinkney & Walker, 2020). For the most part, this seems to be connected to the level of societal stigma attached to the label (Bluff et al, 2012).…”
Section: Theorising the Experiences Of Care‐experienced Students Thro...mentioning
confidence: 99%
See 2 more Smart Citations